2004
DOI: 10.1606/1044-3894.328
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Disruption in Adults with Cognitive Disabilities

Abstract: ome 900,000 people with intellectual or developmental disabilities live in residential facilities in the United States, and many more are on waiting lists or are expected to need residential services in their adult years. Most live in small group settings; on average, three people live in each residential facility (Braddock, 2001, as cited in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…These restrictions could result in an infringement of human rights. Similarly, previous research (Knox & Hickson ; Runnion & Wolfer ) found that people with intellectual disabilities faced barriers to having relationships and expressing sexuality.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These restrictions could result in an infringement of human rights. Similarly, previous research (Knox & Hickson ; Runnion & Wolfer ) found that people with intellectual disabilities faced barriers to having relationships and expressing sexuality.…”
Section: Discussionmentioning
confidence: 62%
“…Restrictions, such as not allowing overnight visitors, may be placed by services or families upon people with intellectual disabilities, therefore threatening their identities as adults who are entitled to sexual autonomy (Bernert ). Services can also contribute to this barrier, such as when planning care packages in residential services, but not considering existing relationships (Runnion & Wolfer ). In relation to this, Hollomotz and the Speakup Committee () concluded that people with intellectual disabilities could be at risk if they have a restricted choice of places in which to conduct sexual relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing their sense of dependence on others and enhancing their sense of autonomy are crucial elements of any relevant support. Direct support staff, parents, and policymakers lead reform in this area, by bringing down barriers and enabling persons with ID to experience couple relationships (Burgen & Bigby, ; Runnion & Wolfer, ). Additionally, programs should strive to teach persons with ID social and interpersonal skills relevant to participating in couple relationships (Burgen & Bigby, ; Drew & Hardman, ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to affect changes in this parent-child dynamic and to assist adults with intellectual disabilities in creating and maintaining couple relationships, Abbott and McConkey (2006) suggest that parents adopt a non-judgemental approach towards the matter. Other studies go further to suggest that parents should lead reform in this area by bringing down barriers and actively enabling their children to experience couple relationships (Burgen & Bigby, 2007;Runnion & Wolfer, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Group or individual counselling for parents may help them re-examine their perceptions and strategies in bringing down barriers and providing their adult sons or daughters with intellectual disabilities the support they need for creating and maintaining couple relationships(Abbott & McConkey, 2006;Burgen & Bigby, 2007;Runnion & Wolfer, 2004). As part of preparing their children with intellectual disabilities for adulthood, parents should teach them social and interpersonal skills from a young age.…”
mentioning
confidence: 99%